Evaluating structural and performance dynamics of a differentiated U.S. apple industry - Hu, Wenjing, author; Thilmany, Dawn D., advisor; Pendell, Dustin L., committee member; Davies, Stephen P., committee member; Pena, Anita Alves, committee member (Colorado State University. Libraries, 2012)
There is a growing public interest, and consequently, support for public policies and programs to support local food systems. These programs aim to inform consumers about the potential benefits of local foods and influence consumers' choice among differentiable foods. As state promotion and marketing programs have been widely adopted throughout the country, demand for local produce and market opportunities for locally-branded products have increased significantly. Local promotion programs have also started to influence the structure of markets, as demand has stimulated a proliferation of localized, direct marketing supply chains linking growers directly to consumers. However, there are few true examinations focused on the welfare implications surrounding the restructuring of food markets and or the underlying economic performance of market innovations. The main objective of this study is to explore the structural and performance dynamics of a market as a result of new labeling efforts and promotional campaigns, highlighting the availability of locally grown products (both in direct markets and within more conventional marketing channels). This study develops a partial equilibrium displacement model for Colorado apples to analyze the impacts of local labeling. The information obtained from the result of this model informs how consumer perceptions and marketing channel structure influence market performance. To complement the broader analysis, the market structure and price relationship at different market levels are examined. The results showed that the Southwest and Northeast retail markets dominated national retail markets and the Northwest retail market dominated western retail markets in terms of its influence on retail prices. Not surprisingly the Yakima Valley and Wenatchee District in Washington significantly affected the price formation process of all other shipping points. If the unknown transaction cost band is allowed to vary according to transportation costs and seasonality, it may more closely mimic suppliers who view more opportunities to adjust their supply between regional markets in search of potential profits. Overall, local labeling increases consumers' willingness to pay for local apples relative to domestic apples in Colorado, and subsequently, demand will shift toward local apples and the supply will shift toward direct markets in Colorado. In terms of producer surplus, Colorado suppliers for direct markets gain while Colorado suppliers for shipping points lose in short run. In the long run, both suppliers will gain but the suppliers for direct markets will gain more than the suppliers for shipping points. Overall, the Colorado producers lose in the short run while they gain in the long run.
Keywords: equilibrium displacement model; local food; marketing channel; market relationship; threshold autoregressive model; welfare analysis